1998
DOI: 10.1126/science.280.5366.1082
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP, a Ras Guanyl Nucleotide- Releasing Protein with Calcium- and Diacylglycerol-Binding Motifs

Abstract: RasGRP, a guanyl nucleotide-releasing protein for the small guanosine triphosphatase Ras, was characterized. Besides the catalytic domain, RasGRP has an atypical pair of "EF hands" that bind calcium and a diacylglycerol (DAG)-binding domain. RasGRP activated Ras and caused transformation in fibroblasts. A DAG analog caused sustained activation of Ras-Erk signaling and changes in cell morphology. Signaling was associated with partitioning of RasGRP protein into the membrane fraction. Sustained ligand-induced si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
526
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(550 citation statements)
references
References 24 publications
19
526
0
5
Order By: Relevance
“…The identities of the Ser316 kinase and Ser325 phosphatase acting downstream of PKC have yet to be identified but these studies have ruled out PKA and mitogen-activated protein kinases in this process. In addition to the phorbol ester-binding PKC isoenzymes, PMA has been reported to bind other receptors such as the chimaerins (Caloca et al, 1999), Ras guanyl-releasing protein (ElShemerly et al, 1997;Ebinu et al, 1998) and protein kinase Ds (Van Lint et al, 2002). Importantly, this study and previous studies (Legg et al, 2002) have demonstrated that the effects of PMA treatment on CD44 Ser316 phosphorylation and Ser325 dephosphorylation are mediated via activation of PKC as the PKC inhibitors Ro-31 and Bis-I are effective in blocking these phosphorylation/dephosphorylation events.…”
Section: Discussionmentioning
confidence: 99%
“…The identities of the Ser316 kinase and Ser325 phosphatase acting downstream of PKC have yet to be identified but these studies have ruled out PKA and mitogen-activated protein kinases in this process. In addition to the phorbol ester-binding PKC isoenzymes, PMA has been reported to bind other receptors such as the chimaerins (Caloca et al, 1999), Ras guanyl-releasing protein (ElShemerly et al, 1997;Ebinu et al, 1998) and protein kinase Ds (Van Lint et al, 2002). Importantly, this study and previous studies (Legg et al, 2002) have demonstrated that the effects of PMA treatment on CD44 Ser316 phosphorylation and Ser325 dephosphorylation are mediated via activation of PKC as the PKC inhibitors Ro-31 and Bis-I are effective in blocking these phosphorylation/dephosphorylation events.…”
Section: Discussionmentioning
confidence: 99%
“…First, the recent discovery of cAMPregulated Rap1GEFs (DeRooij et al, 1998;Kawasaki et al, 1998) establishes the precedent for the existence of cAMP-regulated RasGEFs, although to our knowledge these have not yet been described. It is intriguing, however, that novel calcium-activated RasGEFs have been identiÂźed (Ebinue et al, 1998;Farnsworth et al, 1995). Second, the e ects of cAMP on Ras activity could be mediated through e ects on GAP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Major RasGEFs in T cells are Sos (son of sevenless) and RasGRP1 (Ras guanine nucleotide releasing protein 1) [19,20]. RasGRP1 has a DAG-binding C1 domain and a pair of EF hand motifs that bind to Ca 2+ directly [21]. RasGRP1 localizes in the cytoplasm of resting T cells and translocates to the Golgi apparatus in response to weak stimulation, such as with soluble anti-CD3 antibodies or with low-affinity peptides that induce positive selection of thymocytes [22,‱‱23].…”
Section: Integration and Crosstalk Between Ca 2+ And Other Signallingmentioning
confidence: 99%